RARE-EARTH ELEMENTS IN EOLIAN AND RIVER SUSPENSIONS IN THE REGION OF LAKE BAIKAL - Bobrov V.A.; Khodzher T.V.; Granina L.Z.; Mel'gunov M.S.; Kolmogorov Yu.P.; Poslovin A.L. (My University, 2001)
Neutron-activation analysis with the use of the X-ray fluorescence method permitted us to determine a number of rock-forming and trace elements in the samples of atmospheric aerosol collected on air filters and in snow samples taken in the period 1980-97. Based on their REE patterns, we have estimated the role of global and regional supply of finely dispersed detritus in the sedimentation in Lake Baikal. A comparative analysis of the elemental composition of suspensions of the main rivers feeding the lake was performed. The earlier and newly determined contents of REE, Fe, Hf, Th, and Rb in the samples are compared with the clarkes of these elements in continental clays.